The Transformation of Communication Patterns in Tesabela Village: A Social Collectivity Perspective - Bacotang Bacotang; Idris Idris; Arifin Arifin (Labor Jurusan Sosiologi Fakultas Ilmu Sosial Universitas Negeri Padang, 2026)
The development of digital technology and increasing social mobility have changed the communication patterns of rural communities and have the potential to impact the sustainability of collective values that form the basis of social life. This study aims to analyze the shifting forms of communication patterns in the Tesabela Village community, the dynamics of social collectives that occur, and their implications for the sustainability of community values of togetherness. The study used a qualitative approach with a purposive sampling technique in selecting informants consisting of traditional leaders, religious leaders, youth leaders, and village officials who understand the social dynamics of the community. The number of informants was 8 people. Data were collected through in-depth interviews and analyzed descriptively-interpretively. The results of the study indicate that community communication patterns have shifted from symbolic-communal communication based on direct interaction to more personal, administrative, and supported by digital technology. However, social collective values have not disintegrated, but have transformed into a more contextual and situational form. Social solidarity is no longer built through routine daily interactions, but is actualized in social moments that have cultural significance. The novelty of this research lies in the finding that shifts in communication patterns in rural communities do not automatically lead to individualism, but rather give rise to new forms of social collectivity that adapt to technological developments and lifestyle changes. This finding enriches the study of the sociology of communication by demonstrating that digital communication transformation can go hand in hand with the sustainability of collective values in rural communities.